Engineering a biomimetic bone scaffold that can regulate redox homeostasis and promote osteogenesis to repair large bone defects. (July 2022) - Mac, Cam-Hoa; Chan, Hao-Yu; Lin, Yi-Hsuan; Sharma, Amit Kumar; Song, Hsiang-Lin; Chan, Yi-Sheng; Lin, Kun-Ju; Lin, Yu-Jung; Sung, Hsing-Wen
Abstract: The reconstruction of a large bone defect to an extent that exceeds its self-healing capacity has been a great clinical challenge. In pursuit of this goal, a biomaterial-based scaffold that comprises radially aligned mineralized collagen (RA-MC) fibers that incorporate nanosilicon (RA-MC/nSi), is proposed. The chemical composition of the MC fibers is similar to that of natural bone matrices. The therapeutic efficacy of the RA-MC/nSi scaffold is evaluated in a mouse model with an experimentally created large calvarial defect. In vitro and in vivo results reveal that the RA-MC fibers of the scaffold guide the directional infiltration and migration of reparative cells from the host tissue toward the center of the defect, suggesting a potential application in promoting osteoconductivity. The incorporated nSi renders the scaffold able sustainably to release gaseous hydrogen and water-soluble silicic acid during the healing process. The released hydrogen gas can effectively regulate redox homeostasis and mitigate excessive inflammation, and the silicic acid can promote the proliferation of reparative cells and enhance their osteogenic differentiation, indicative of osteoinductivity. These findings support the use of the as-proposed biomimetic RA-MC/nSi scaffold as a promising bone substitute to enhance the regeneration of large bone defects.